2001
DOI: 10.1073/pnas.091094798
|View full text |Cite
|
Sign up to set email alerts
|

Tracking memory's trace

Abstract: There is strong converging evidence that the intermediate and medial part of the hyperstriatum ventrale of the chick brain is a memory store for information acquired through the learning process of imprinting. Neurons in this memory system come, through imprinting, to respond selectively to the imprinting stimulus (IS) neurons and so possess the properties of a memory trace. Therefore, the responses of the intermediate and medial part of the hyperstriatum ventrale neurons to a visual imprinting stimulus were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 48 publications
(69 reference statements)
7
61
0
Order By: Relevance
“…In one study, the maximal proportion of ISselective neurons was observed at 25 h after IS exposure. The largest increase in ISselective neurons occurred between 8 and 25 h after exposure, which indicated a possible role of sleep in the consolidation of the IS memory (Horn et al 2001). Later work confirmed the necessity of sleep.…”
Section: Sleep and Developmental Song Learning In Zebra Finchesmentioning
confidence: 82%
“…In one study, the maximal proportion of ISselective neurons was observed at 25 h after IS exposure. The largest increase in ISselective neurons occurred between 8 and 25 h after exposure, which indicated a possible role of sleep in the consolidation of the IS memory (Horn et al 2001). Later work confirmed the necessity of sleep.…”
Section: Sleep and Developmental Song Learning In Zebra Finchesmentioning
confidence: 82%
“…Experimental analysis in an animal model for filial imprinting (Lorenz, 1935;Hess, 1959), that is, the very first neonatal emotional learning event in vertebrates including human and nonhuman primates, which results in the formation of an emotional bond to the mother or caregiver, has revealed dramatic changes of synaptic connectivity in prefrontal forebrain regions in relation to this learning process. Domestic chicks, which were imprinted on an artificial acoustic or visual stimulus representing the mother, showed increased synaptic densities in an associative forebrain region (Horn, Bradley, & McCabe, 1985;Horn, Nicols, & Brown, 2001) but decreased densities of excitatory spine synapses in two other higher associative forebrain regions (Bock & Braun, 1998, 1999aWallhausser & Scheich, 1987). The reduction of spine synapses which was observed after acoustic filial imprinting critically depends on the activation of glutamatergic NMDA receptors (Bock, Schnabel, & Braun, 1997;Bock & Braun, 1999a), and appears to reflect a synaptic network which responds with a potentiated response upon recall of the learned, emotionally relevant stimulus.…”
Section: Impact Of Early Emotional Experience On Synaptic Reorganizatmentioning
confidence: 99%
“…In an earlier electrophysiological study, Horn and collaborators (Horn et al, 2001;Horn, 2004) enquired whether there was evidence for strengthening Hebbian 'neural assemblies' (Hebb, 1949) in the IMM during imprinting. Such neural assemblies would involve functional coupling between neurons that respond to the imprinting stimulus.…”
Section: Neural Mechanisms Of Memory Consolidation During Sleepmentioning
confidence: 97%